2014 interpretation and application of international financial reporting standards - Mackenzie, Bruce (Hoboken, N.J. : Wiley, 2014)
Suitable for understanding International Financial Reporting Standards, this book provides the necessary tools for understanding the IASB standards and offers practical guidance and expertise on how to use and implement them.
Includes index
Keywords: Financial statements -- Standards